2005
DOI: 10.1385/bter:107:2:153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Zinc Levels on the Activities of Enzymes, Weights of Organs, and the Concentrations of Zinc and Copper in Growing Rats

Abstract: Zinc (Zn) is an essential nutrient that is required in humans and animals for many physiological functions, including immune and antioxidant function, growth, and reproduction. The present study was performed to investigate the effects of three Zn levels, including Zn adequate (35.94 mg/kg, as a control), Zn deficiency (3.15 mg/kg), and Zn overload (347.50 mg/kg) in growing male rats for 6 wk. This allowed for evaluation of the effects that these Zn levels might have on body weight, organ weight, enzymes activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
31
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
9
31
1
Order By: Relevance
“…Yu et al (2010) found that the chelation of zinc by low molecular weight ligands leads to the formation of a soluble complex that can increase Zn absorption. The activity of ALP was greatly increased by Zn addition regardless of sources in this study which is in agreement with other studies (Sun et al 2005;Rocha et al 2015). The Cu-ZnSOD, in which Zn is an integral part, is an important antioxidant defense in nearly all living cells exposed to oxygen (Paz Matias et al 2014).…”
Section: Discussionsupporting
confidence: 94%
“…Yu et al (2010) found that the chelation of zinc by low molecular weight ligands leads to the formation of a soluble complex that can increase Zn absorption. The activity of ALP was greatly increased by Zn addition regardless of sources in this study which is in agreement with other studies (Sun et al 2005;Rocha et al 2015). The Cu-ZnSOD, in which Zn is an integral part, is an important antioxidant defense in nearly all living cells exposed to oxygen (Paz Matias et al 2014).…”
Section: Discussionsupporting
confidence: 94%
“…However, the exact mechanism underlying this regulation remains to be determined. In the present study, food intake was suspected to decrease dramatically in the ZD group, because it has been reported that a zinc-deficient diet causes severe growth retardation and a reduction in food intake (46,47). As the PF group was fed according to the food intake of the ZD group, the intake of the PF group was thought to be severely limited; as a result, the PF group appeared to change its requirements for several minerals and a stress response was triggered.…”
Section: Discussionmentioning
confidence: 71%
“…These findings indicate that excessive intake of zinc supplements have also potential risk to humans [6]. Reports of the studies examining the zinc effects with different doses on healthy rats are limited and more studies are needed [6,31]. Reseachers observed that zinc deficiency was not only related with the ethanol intake directly but also dependent on the level of the liver damage [3].…”
Section: Discussionmentioning
confidence: 99%